Effect of jackfruit seed extract (artocarpus heterophyllus) concentration on corrosion inhibition of galvanized steel in seawater - Sudirmansyah Lubis; Muhammad Sayuti; Muhammad Muhammad; Rizka Mulyawan; Nurul Islami (Jurnal Polimesin, 2025)
This study confirms that immersion time and inhibitor concentration significantly affect the corrosion rate of galvanized steel in seawater. Without an inhibitor (0% concentration), the corrosion rate progressively increases, reaching a maximum of 0.4395 mpy after 30 days. In contrast, the addition of jackfruit seed extract effectively reduces corrosion, with the lowest rates observed at 0.0441 mpy (2%), 0.0330 mpy (4%), and 0.0192 mpy (6%) after 30 days. These results highlight the high efficiency of jackfruit seed extract as a natural corrosion inhibitor, demonstrating that higher concentrations and longer immersion times enhance corrosion protection. This study suggests that jackfruit seed extract is a viable, eco-friendly alternative to synthetic inhibitors, offering a sustainable solution for corrosion prevention in marine environments. Further research on long-term stability and large-scale applications is recommended to optimize its industrial implementation.